Measurement of radon gas concentration in water and soil samples in AL-Najaf governorate by using nuclear track detector (CR-39) (Baghdad Science Journal, 2015)
The radon gas concentration in environmental samples soil and water of selected regions in Al-Najaf governorate was measured by using alpha-emitters registrations which are emitted form radon gas in (CR-39) nuclear track detector. The first part is concerned with the determination of radon gas concentration in soil samples, results of measurements indicate that the highest average radon concentration in soil samples was found in (Al-Moalmen) region which was (100.0±7.0 Bq/m3), while the lowest average radon concentration was found in (Al-Askary) region which was (38.5±4.7 Bq/m3), with an average value of (64.23±14.9 Bq/m3) ,the results show that the radon gas concentrations in soil is below the allowed limit from (ICRP) agency which is (200 Bq/m3), while the radon exhalation rate (RER) ranged from (35.23-91.52 µBq/m2h), and average value which was (58.77±13.6 µBq/m2h). The second part is concerned with the determination of radon gas concentration in samples of tap water obtained from networks in dwellings in Al-Najaf governorate, the results indicate that the highest average radon concentration in water samples was found in (Meassan) region which was (0.59±0.08 Bq/L), while the lowest average radon concentration was found in (Al-Jamhorah) region which was (0.16±0.04 Bq/L), with an average value of (0.36±0.1 Bq/L), the present results show that the radon gas concentrations in tap water is below the allowed limit from (ICRP) agency which is (0.5994 Bq/L), while the radon exhalation rate (RER) ranged from (2.15-0.58 ?Sv/y), and average value which was (1.28±0.31 ?Sv/y).